Anti-oxidant and antibacterial activities of novel N-sulfonylphtalimide in an ovalbumin-induced inflammation in Wistar rats: Novel N-Sulfonylphthalimide activities in asthma model - Silini, Ilhem; Rouibah, Zineb; Bouraoui, Houda; Ahmida, Meriem; Nedjai, Sabrina; Grib, Ismahene; Berredjem, Malika; Djahoudi, Abd El Ghani; Messarah, Mahfoud; Boumendjel, Amel (Cellular and Molecular Biology, 2024)
Phthalimide and N-substituted phthalimide have a special structure that helps them to be pharmaceutically useful and biologically active. In this study, we investigated the antioxidant, anti-inflammatory and antibacterial effects of a synthetic phthalimide-containing derivative in an experimental asthma model. In vitro determination of antioxidant and chelating activity was carried out by spectrophotometric methods. The in vivo antioxidant activity was carried out in Wistar rats sensitized to ovalbumin in the experimental model of asthma. Our results reveal that that the synthesized N-sulfonylphthalimide molecule has a scavenging capacity against the free radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH•) and a chelating activity on ferrous ions and revealed its protective capacity against altered markers of oxidative stress in the experimental asthma model. All the previous results were confirmed by the result of the histopathological study of the liver. Moreover, neo-synthesized N-sulfonylphthalimide 2 showed antibacterial activity against Gram-positive and Gram-negative bacteria with interesting MIC values. Finally, our study highlights the anti-inflammatory, anti-asthmatic and antibacterial effects of the N-sulfonylphthalimide molecule, which could potentially be a drug of choice in asthmatic pathology, especially during bacterial superinfections in the respiratory tract.